Internationalization from the perspective of Heritage Education: a Latin American Music Education project (Orfeu, 2021)
This text presents some of the reflections carried out based on the actions of an internationalization project developed in partnership between two higher education institutions from two Latin American countries: Brazil and Chile. The project was developed between the years 2018 and 2019. Both the proposals and the possibilities were based on the principles of Contemporary Heritage Education and the idea of ​​internationalization as proposed by Kertz-Welzel (2018). As a result, an analysis of the actions carried out allows us to say that internationalization, when they start from collaborative planning that emerges from integration with participating communities, is consolidated in an educational process of, identification and appreciation of heritage that break limits, forms the construction of communities culturally related and globally connected artistic practices.
Keywords: Cultural heritage; Artistic practices; International projects; Art education; Musical practices